2002
DOI: 10.1021/ol027257h
|View full text |Cite
|
Sign up to set email alerts
|

2-Deoxy-2-iodo-β-glucopyranosyl Fluorides:  Mild and Highly Stereoselective Glycosyl Donors for the Synthesis of 2-Deoxy-β-glycosides from β-Hydroxy Ketones

Abstract: 2-Deoxy-2-iodo-beta-glucopyranosyl fluoride 14 is a highly stereoselective glucopyranosyl donor that may be activated under mild conditions. Application of this new glycosyl donor to the glycosidation reactions of a variety of acceptors including beta-hydroxy ketones affords beta-glycosides with high efficiency and stereoselectivity. [reaction--see text]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…For example, Blanchard and Roush 309 described the application of 2-deoxy-2-iodo-β-glucopyranosyl fluoride 253 , which contains a C6-bromo substituent. The halo-containing glycosyl donor could be activated under mild conditions.…”
Section: Organocatalysis Applied To Deoxyglycoside Synthesismentioning
confidence: 99%
“…For example, Blanchard and Roush 309 described the application of 2-deoxy-2-iodo-β-glucopyranosyl fluoride 253 , which contains a C6-bromo substituent. The halo-containing glycosyl donor could be activated under mild conditions.…”
Section: Organocatalysis Applied To Deoxyglycoside Synthesismentioning
confidence: 99%
“…further demonstrated that the iodo‐substituent at the C‐2 position well controlled the stereochemistry of the newly formed glycosidic bond 11. This character was further illustrated in the glycosylation of 2‐deoxy‐2‐halo‐glycosyl trifluoroacetimidtaes,8a trichloroacetimidates,12ac thioethers,12d,e and fluorides,12f,g which provided the corresponding 2‐deoxy‐2‐halo‐glycosides, and after reductive removal, the 2‐deoxy‐glycosides with high stereroselectivity. Meanwhile, the use of oxidative coupling of glycals in the preferential synthesis of 2‐deoxy‐2‐halo‐α‐glycosides was developed by Lemieux,13a Tatsuta,13b Thiem,13c,d Kessler,13e and Danishefsky,13f respectively.…”
Section: Methodsmentioning
confidence: 92%
“…[4] The lack of stereo-directing group at C2 position makesi tm ore arduous task to control the desired stereochemical outcome at the anomeric center.N evertheless, there are severalw ell documenteds ynthetic methods availablei nt he literature for making 2-deoxyglycosides. First, indirect approach-where temporary participating/non-participating functionality such as -Br, [6] -I, [7] -SR, [8] -SePh, [9] -OAc [10] is introduced at C2-position to control the stereochemical outcomea tt he anomeric position. Literature survey disclosed two approaches have mainly been adopted for stereochemical syntheses of 2-deoxyglycosides.…”
Section: Introductionmentioning
confidence: 99%
“…Literature survey disclosed two approaches have mainly been adopted for stereochemical syntheses of 2‐deoxyglycosides. First, indirect approach‐ where temporary participating/non‐participating functionality such as ‐Br, ‐I, ‐SR, ‐SePh, ‐OAc is introduced at C2‐position to control the stereochemical outcome at the anomeric position. The major roadblocks of these approaches are the requirements of additional synthetic steps: installation followed uninstallation of the temporary group after the desired operation, which eventually decreases the overall efficacy of the reactions.…”
Section: Introductionmentioning
confidence: 99%